﻿Caracterização limnológica e determinação da capacidade suporte do reservatório mendubim, (Rio Grande do Norte) para o cultivo de peixes em tanques-rede - Rocha, Ana Catarina de Lima (2008)
﻿The aims of this study were: i) assessing the trophic state of the Mendubim reservoir (semi-arid, Rio Grande do Norte, Brazil; 05° 38 99,0 S 36°55 98,0 W) based on chlorophyll-a, total phosphorus and nitrogen concentrations and water transparency; ii) relating the patterns of temporal variation of zooplankton and phytoplankton to the trophic state of the reservoir and iii) investigating the carrying capacity of the reservoir for cage fish farming. The samplingwas done monthly from July 2006 to July 2007 in three stations at the reservoir: next to the dam (barrage), in the central region and in the mouth of the main tributary. The abiotic and biotic variables analyzed were: Secchi depth, volatiles and fixed suspended solids, chlorophyll-a, total phosphorus and nitrogen, TN:TP ratio and mesozooplankton and phytoplankton composition and biomass. The results showed that the reservoir can be considered as mesotrophic with mean concentrations of total nitrogen, phosphorus and chlorophyll-a equal to 1711, 1 μg.L-1, 30,8 μg.L-1 and 5,62 μg.L-1 respectively. The Cyanophyceae class was the most representative in terms of density, with the presence of potentially toxic species such as Microcystis aeruginosa, Planktothrix planctonica, Cylindrospermopsis raciborskii, Aphanizomenon sp. ,Aphanocapsa delicatissima and Pseudanabaena acicularis. Among the zooplankton, the genus Notodiaptomus presented the largest biomass values. Overall, our results show that the light limitation should explain the weak relationship between chlorophyll-a and total phosphorus and nitrogen concentrations. We concluded that the water of Mendubim reservoir is suitable for intensive fish cage aquaculture. Based on the carrying capacity calculations for this reservoir, we found that the maximum sustainable yield of tilapias in cages in the reservoir is 126 ton per year assuming a factor of food conversion of 1.5: 1.0 and a phosphorus content in the fish food of 1%